Possibilities for the Application of Alternative Dispute Resolution Methods in the Administrative Procedure - Hohmann, Balázs (European Journal of Multidisciplinary Studies, 2018)
The public administration, in particular to the administrative procedure follows a firm objective: to create of the customer friendly approach. Also, there is more and more emphasis recently on improving the efficiency and speed of the procedure. These are the two most important keywords of the decision planning and documentation. The aim of the research in this scientific paper is to detect and analyse the decision-making methods, concurrently being ready to incorporate them into the national administrative procedure systems. These methods are to provide lawful and effectively applicable alternative dispute settlement methods ready to use in Hungarian legal system and also to assist - apart form the aim to reach the basic aims of the administrative procedure - to create a fundament of the decisions made by the authority, having regard to circumstances in real life cases, viewpoint of customers and other parties, and the balance of the public interest. The scope of the paper also covers the theoretical and practical aspects of general mediation and mediation in administrative procedure, in view with the appearance of the topic within the renewing and current administrative procedural law regime. While examining the mediation in administrative procedure in a novel point of view, this work also analyses the role of this special type of mediation in terms of efficiency and charactesistics of the current and future legal solutions in administartive cases often involving parties with adverse interests. Conclusions and proposions in the paper may provide contribution to the spreading and correct treatment of alternative decision making methods in the administrative procedure. The publication of this scientific paper supported by the the Ministry of Justice (Hungary) in the program of increasing of the quality of Hungarian legal studies.